Postharvest Spectral Light Composition Affects Chilling Injury in Anthurium Cut Flowers - Aliniaeifard, Sasan; Falahi, Zahra; Dianati Daylami, Shirin; Li, Tao; Woltering, Ernst (Frontiers in Plant Science, 2020)
The effect of the lighting environment during postharvest storage of ornamentals has largely been neglected in previous research. Anthurium is a cold-sensitive species originating from tropical climates which is widely cultivated all around the world for its ornamental value of the colorful spathes. To investigate the effects of light spectrum on the performance of Anthurium cut flowers under cold storage, two Anthurium cultivars [Calore (red spathe) and Angel (withe spathe)] were placed at low temperature (4 ºC), either in darkness (D) or under different light spectra [red (R), blue (B), 70:30% red:blue (RB) and white (W)] at an intensity of 125 µmol.m-2.s-1. In both cultivars, longest and shortest vase lives were observed in spathes exposed to R and B spectra, respectively. In both cultivars, electrolyte leakage (EL) of spathe was highest under B and W spectra and lowest under R spectrum. Highest rate of flower water loss from the spathes was observed under B-containing light spectra, whereas the lowest rate of water loss was observed in D and under R spectrum. Negative correlations were observed between EL and vase life and between anthocyanin concentration and EL for both Anthurium cultivars. A positive correlation was found between anthocyanin concentration and vase life. For both Anthurium cultivars, spectral light composition with higher percentage of B resulted in higher EL and as a result shorter vase life in cut flowers under cold storage condition. The adverse effect of B light spectrum on vase life of Anthurium can be explained through its effect on water loss and on oxidative stress and membrane integrity. The importance of both mechanisms is discussed. Quality of Anthurium cut flowers should benefit from environments with restricted B light spectrum during postharvest handling.